Factors Affecting Academic Burnout in College Students: Scoping Review - Wardhana, Lauren David Rangga; Yoenanto, Nono Hery; Fardhana, Nur Ainy (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Academic burnout is a condition where individuals feel fatigue caused by academic demands, have pessimistic feelings about themselves and lack of interest in their studies and feel themselves as incompetent students. The purpose of this scoping review is to determine the factors that can affect academic burnout. The method used is scoping review. The articles reviewed were research articles ranging from 2019-2024, international journals with a sample of students, and research articles with correlation and regression methods traced through the Scopus, ProQuest, and Clarivate Web of Science databases using the PRISMA method. Based on the 15 research articles reviewed, it is known that academic burnout is influenced by several internal factors and external factors. Internal factors include: academic self-efficacy, academic motivation, and personality. External factors include: social support, campus climate, physical activity, academic stress, health status, living habits, demographic factors, emotional exhaustion, stress, and academic achievement. The implications of this study can be a reference for further research in determining the independent variables that influence academic burnout. Academic burnout adalah adalah ketika seseorang merasa lelah karena tuntutan akademik, memiliki perasaan pesimis terhadap diri sendiri serta kurangnya ketertarikan pada studi yang dijalani dan merasa dirinya sebagai mahasiswa yang tidak berkompeten. Scoping review bertujuan untuk mengidentifikasi faktor-faktor yang dapat mempengaruhi kebosanan akademik. Artikel penelitian yang dievaluasi berkisar dari 2019 hingga 2024, jurnal internasional dengan sampel yaitu mahasiswa, dan artikel penelitian dengan metode kolerasi serta regresi yang ditelusuri melalui database Scopus, ProQuest, dan Clarivate Web of Science dengan menggunakan metode PRISMA. Berdasarkan 15 artikel penelitian yang ditinjau diketahui bahwa academic burnout dipengaruhi oleh beberapa faktor internal dan faktor eksternal. Faktor internal, meliputi: academic self efficacy, motivasi akademik, dan kepribadian. Faktor eksternal, meliputi: dukungan sosial, iklim kampus, aktivitas fisik, stres akademik, status kesehatan, kebiasaan hidup, faktor demografis, kelelahan emosional, stress, dan prestasi akademik. Implikasi temuan penelitian ini akan digunakan sebagai referensi untuk studi lanjutan yang akan menentukan variabel independen yang mempengaruhi academic burnout.